1996
DOI: 10.1002/(sici)1096-8628(19961122)67:6<564::aid-ajmg10>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking dysfunction is a putative phenotypic susceptibility marker of schizophrenia and maps to a locus on chromosome 6p in families with multiple occurrence of the disease

Abstract: The difficulties in defining the borders of the schizophrenia spectrum is one major source of variance in linkage studies of schizophrenia. The employment of biological markers may prove advantageous. Due to empirical evidence, eye tracking dysfunction (ETD) has been discussed to be the most promising marker for genetic liability to schizophrenia. With respect to the recent progress in genomic scans, which have pointed to the short arm of chromosome 6, we carried out a scan of the 6p21-23 region with 16 micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(56 citation statements)
references
References 41 publications
2
54
0
Order By: Relevance
“…For example, the QT elongation on electrocardiogram was used to discover the genes underlying the long QT syndrome, characterized by syncope, ventricle arrhythmias, and sudden death (Keating and Sanguinetti, 2001). In the field of psychiatry, disturbances of P50 auditory evoked response and smooth pursuit eye movements are among the best established endophenotypes present in schizophrenic patients and their unaffected relatives, and linkage studies have already identified the loci involved in chromosome 15q (Freedman et al, 1997) and 6p (Arolt et al, 1996), respectively. In OCD, stratification by 5-HT level could decrease genetic heterogeneity and increase power to identify susceptibility genes in association and linkage studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the QT elongation on electrocardiogram was used to discover the genes underlying the long QT syndrome, characterized by syncope, ventricle arrhythmias, and sudden death (Keating and Sanguinetti, 2001). In the field of psychiatry, disturbances of P50 auditory evoked response and smooth pursuit eye movements are among the best established endophenotypes present in schizophrenic patients and their unaffected relatives, and linkage studies have already identified the loci involved in chromosome 15q (Freedman et al, 1997) and 6p (Arolt et al, 1996), respectively. In OCD, stratification by 5-HT level could decrease genetic heterogeneity and increase power to identify susceptibility genes in association and linkage studies.…”
Section: Discussionmentioning
confidence: 99%
“…Two independent studies found significant linkage of eye tracking phenotype to loci on chromosome 6p21 (Arolt et al, 1996;Matthysse et al, 2004). Association with COMT and DRD3 genes reported (Thaker et al, 2004;Rybakowski et al, 2001).…”
Section: A Paradigm Shift To Facilitate Drug Discoverymentioning
confidence: 99%
“…47,48 In light of the immunological theory of schizophrenia, the MHC has long been proposed as a candidate locus that may influence the susceptibility to schizophrenia. The MHC spans approximately 4 million base pairs of DNA and has been mapped to 9 Linkage studies have also suggested that there may be at least one locus on chromosome 6p that affects susceptibility to schizophrenia, [10][11][12][13][14] eye-tracking dysfunction, 15 and/or the severity of positive symptoms. 16 There are many genes of potential interest in MHC region that demonstrated association with schizophrenia phenotypes in previous studies-NOTCH4, [49][50][51][52] TNXB, 53 DRB1, 54-57 DQB1.…”
Section: Discussionmentioning
confidence: 99%
“…9 Linkage studies also suggest there may be one or more loci on chromosome 6p that affect susceptibility to schizophrenia. [10][11][12][13][14] In addition, there is some evidence that genetic loci on chromosome 6p may influence the manifestation of the endophenotype of eye-tracking dysfunction 15 and modify the severity of positive symptoms in affected subjects. 16 An example of the utility of stratifying linkage data set on the basis of HLA genotypes (DR3 and DR4) was demonstrated in the successful identification of a causative locus for Type I diabetes mellitus on chromosome 11q, 17 a finding that was confirmed by other linkage 18,19 and linkage disequilibrium studies.…”
mentioning
confidence: 99%